The Fission-Based 99Mo Production Process ROMOL-99 and Its Application to PINSTECH Islamabad - Rudolf Muenze; Gerd Juergen Beyer; Richard Ross; Gerhard Wagner; Dieter Novotny; Erik Franke; Mustansar Jehangir; Shahid Pervez; Ahmad Mushtaq (Science and Technology of Nuclear Installations)
An innovative process for fission based 99Mo production has been developed under Isotope Technologies Dresden (ITD) GmbH (former Hans Wälischmiller GmbH (HWM), Branch Office Dresden), and its functionality has been tested and proved at the Pakistan Institute of Nuclear Science and Technology (PINSTECH), Islamabad. Targets made from uranium aluminum alloy clad with aluminum were irradiated in the core of Pakistan Research Reactor-1 (PARR-1). In the mean time more than 50 batches of fission molybdenum-99 (99Mo) have been produced meeting the international purity/pharmacopoeia specifications using this ROMOL-99 process. The process is based on alkaline dissolution of the neutron irradiated targets in presence of NaNO3, chemically extracting the 99Mo from various fission products and purifying the product by column chromatography. This ROMOL-99 process will be described in some detail.